The influence of opinion leaders on consumer buying behavior among millennials in Klang Valley - Kong, Chee Kei; Osman, Syuhaily (Malaysian Consumer and Family Economics Association, 2024)
Opinion leaders have emerged as individuals with social influence who serve as the core of an interpersonal communication network. The social trends have made opinion leaders significantly influence buying behavior, especially among millennials. A deeper understanding of the characteristics of opinion leadership is still needed and based on the two-step flow theory, we developed a research framework to study opinion leaders’ influence (trust, credibility, and originality) on consumer buying behavior. A simple random sampling method was used, and the sample comprised 398 millennials in Klang Valley, Malaysia. Data were collected via a self-administered questionnaire. Regarding the relationships involving the opinion leaders’ elements, Pearson correlation analysis found that the trust (r=0.545; p=0.00), credibility (r=0.518; p=0.00), and originality (r=0.398; p=0.00) of opinion leaders are significantly related to consumer buying behavior. Multiple regression analysis was then applied to examine the most influential opinion leader factors on millennials’ buying behavior. The result showed that this model contributed a total of 30.7% and that trust (β = 0.368, p = 0.000) is the most influencing factor on millennials buying behavior. Marketers will have an updated perspective on the influence of opinion leaders on consumer buying behavior knowing the profiles of opinion leaders is extremely beneficial for consumers to make wise purchase decisions.